Conversion Therapy. Reflections on the Topic - Коcharyan , Garnik S. (Psychological Counseling and Psychotherapy, 2022)
Currently, there are two approaches to the therapy of ego-dystonic homosexuals. According to the first approach (gay affirmative therapy), they need to be adapted to their sexual desire. According to the second approach (conversion / reparative therapy), it is necessary to help patients change their sexual orientation in accordance with their desire and rejection of homosexuality and a homosexual lifestyle for themselves. Each approach has its supporters. Ego-dystonic homosexuality, which was included in the list of mental disorders in ICD-10, was not included in this list in ICD-11. In some countries, conversion therapy is outlawed because homosexuality is supposedly inborn and its correction looks akin to trying to change racial or national identity. However, in many countries of the world such prohibitions do not exist. The conducted studies indicate the presence of only a slight innate biological predisposition to the formation of homosexuality, while the main role in its development is played by social and psychological factors. Data are given, according to which homosexuality cannot be congenital, but in some cases one can speak of an innate predisposition. However, predisposition is not predestination. Since homosexuality cannot be considered innate, this opens up opportunities for influences that prevent its formation and conversion therapy, which changes the direction of homosexual attraction to heterosexual. It is noted that sexual orientation can change even spontaneously without any efforts of both the person himself and a specially trained specialist. If this is so, then it is quite natural that it can be changed by applying certain psychotherapeutic efforts. The question of the immutability of sexual orientation, in particular, is refuted by the presence of the phenomenon of sexual fluidity. The issue of negative consequences of conversion therapy is considered. It is noted that the possibility of their occurrence is extremely exaggerated. They, in particular, can occur during the forced correction of homosexual attraction, which is currently not carried out in civilized countries. Often, attention is focused on the possibility of complications in the application of electrical discharges, the negative impact of which in this case is greatly exaggerated. When comparing the effects of their use with the effects of electroconvulsive therapy (where uses incomparably stronger electrical discharges), which is not prohibited and is used to treat severe mental disorders, it is concluded that there are double standards based on ideologically driven cognitive distortions. There are a large number of studies proving the effectiveness of conversion therapy. Methods of psychotherapy used to change the direction of sexual desire are named, as well as the experience of the author of the article on the use of conversion therapy. It is concluded that such therapy is effective and has the right to exist. It can be used in ego-dystonic homosexuals who want to get rid of their attraction. Refusal to provide this type of assistance is a violation of human rights.